Cement Deep Soil Mixed Walls/Grout Plug for Groundwater Cut Off and Excavation Support at the Bart Warm Springs Extension - Douglas R. Jenevein; Mitchell L. Fong; Thomas S. Lee; Harry Schnabel (Deep Foundations Institute, 2015)
"The Warm Springs Extension (WSX) is one of a series of projects that will eventually extend the Bay Area Rapid Transit System (BART) from Fremont to San Jose, California. A cut and cover tunnel was used for a portion of the extension that runs through Fremont Central Park to minimize the impacts that an at-grade railway would have on the Park. A cement deep soil mix (CDSM) wall was selected by the engineer as the preferred method of providing structural support and groundwater cut-off for a portion of the tunnel where it passes through an important aquifer and near Lake Elizabeth. In addition to the CDSM wall, a jet grout plug was constructed at the base of the tunnel to provide a complete groundwater cut-off.This paper will discuss the unique quality assurance and quality control measures taken for the soil mix wall and jet grout plug as well as the methods used to repair leaks and mitigate water seepage through the exposed wall and grout plug.PROJECT DESCRIPTIONThe Bay Area Rapid Transit (BART) Warm Springs Extension (WSX) project is located south of the existing Fremont BART station extending 8.9-km (5.4 miles) to Warm Springs District in Fremont, California. The WSX project has been divided into two contracts with different delivery methods. In order to minimize impacts to Fremont Central Park, a subway was selected at this portion of the alignment under a conventional design/bid/build contract.The Fremont Central Park Subway (FCPS) which begins on the south side of Walnut Ave and ends just north of Paseo Padre Parkway and is about 2.3-km (1.4 miles) long. Fig. 1 shows the entire WSX and the FCPS project. The FCPS contract consists of a cut-and-cover subway box, subway transition structures, ventilation structures and a section of which transverses Lake Elizabeth (a man-made lake). The geologic conditions consist of fill (sand, silt, clay and construction debris), Young Alluvium (clay and silt), Basin Deposits (clay, silt, and sand), and Older Alluvium (sand and gravel) as shown in Fig. 2.HYDROGEOLOGY OF THE PROJECT SITEThe FCPS is dominated by two geologic features - the Hayward Fault and the Above Hayward Fault (AHF) aquifer. The AHF aquifer provides a significant source and storage of water for the local water district. The underground subway will penetrate this aquifer and is up to 11m (36 ft) below the groundwater table. No groundwater was allowed to be pumped during construction of the subway box by Alameda County Water District (ACWD). To facilitate excavation for the subway box, temporary cut-off walls and a grout plug were designed to retain and resist high differential hydraulic pressure. The following section describes the selection of a deep soil mixing method for water cutoff. Design of the grout plug has been described in Lee, et al., 2011 and Fong and Lee, 2009, and is not the focus of this paper."